Comparative Outcomes of Robotic-Assisted vs. Conventional Total Knee Arthroplasty - Anwar, Kashif; Asghar, Luqman; Ali Shah, Ghazanfar; Danish Ali, Syed; Adeel, Muhammad; Kabir, Samir Khan (Journal of Neonatal Surgery, 2025)
Background: Robotic-assisted total knee arthroplasty (TKA) has emerged as a precision-enhancing alternative to conventional TKA, yet real-world evidence from low- and middle-income settings remains limited. Objective: This study compares perioperative, radiographic, and early functional outcomes between robotic-assisted and conventional TKA in a tertiary care cohort. Methods: A retrospective comparative study was conducted at Jinnah Postgraduate Medical Center from May 2023 to May 2024 on 138 patients who underwent primary TKA. Patients were assigned to either robotic-assisted (n = 69) or conventional TKA (n = 69) based on operative technique. Demographics, intraoperative parameters, radiographic alignment, postoperative recovery, complications, and 6-month functional outcomes (WOMAC, KSS, satisfaction) were compared. Results: Baseline characteristics were comparable between groups. Robotic TKA had longer operative time (102.6 ± 12.8 vs. 94.2 ± 11.3 min; p < 0.001) but lower blood loss (172 ± 41 vs. 222 ± 58 mL; p < 0.001) and fewer soft-tissue releases (11.6% vs. 27.5%; p = 0.018). Alignment within ±3° of neutral was achieved more frequently in the robotic group (91.3% vs. 72.5%; p = 0.006). Early ambulation (<24 h) and shorter length of stay were more common after robotic TKA (76.8% vs. 58.0%; p = 0.019 and 3.2 ± 0.9 vs. 4.1 ± 1.1 days; p < 0.001, respectively). Six-month WOMAC and KSS scores were significantly better in the robotic group (p = 0.002 and p = 0.001). Conclusion: Robotic-assisted TKA demonstrated superior radiographic precision and improved early recovery and functional outcomes compared to conventional TKA, despite longer operative time. Prospective studies with long-term follow-up and cost-analysis are warranted to define durability and feasibility of broader implementation in resource-limited healthcare systems.